A Multicriteria Policy Analysis: Policy Framework for Sustainable Groundwater Management in Kupang City, East Nusa Tenggara, Indonesia - Bani, Aplonia Nia; Suprihatin, Suprihatin; Saptomo, Satyanto Krido; Kaswanto, Regan Leonardus (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
This study aimed to provide a policy framework for groundwater management in Kupang City, East Nusa Tenggara. The method used in this research was a multicriteria policy analysis method with a qualitative approach. Data were collected using a focus group discussion method. The study participants were 14 stakeholders, including the Director of Planning and Supervision of Watershed Management Nusa Tenggara II River Basin Management Center, Head of the Watershed and Protected Forest Management Center Benain Noelmina, Development Planning Agency, Regional Research and Development of East Nusa Tenggara, Southeast Province, Chair of the River Basin Forum of East Nusa Tenggara Province, Kupang City Development Acceleration Team, Commission III Regional Legislative Council of Kupang City, Non-governmental Organizations, Environmental Practitioners, Provincial Level Environmental Observer Groups, Kupang City and Regency, Legal Practitioners, and Academics. In the focus group discussion, the respondents were free to express their opinions on sustainable groundwater management policies in Kupang City, East Nusa Tenggara. The results show that the groundwater information system is the best in an integratedscenario with a superior program for establishing special zones to identify watershed conservation areas.